Ecological Taxes and Mineral Coal - Galarza, Blanca Lyda Bogota; Quintero, Fernan Alonso Cardona; Gómez, Ricardo Javier Aragón; Polo, Moises Edgardo Meriño; Guzman, Gerardo Andres Moreno (Journal of Posthumanism, 2025)
This article intends to analyze the contribution of the ecological taxes of the mining sector focused on mineral coal to the conservation and preservation of the environment. In the same way, the participation of the resources collected by the National Government is studied through the review of development plans, territorial public finances, the component destined for environmental conservation and the incidences of the tax reform 2022 "For the justice and equity” Law 2277 of 2022.Thus, the municipalities of Lenguazaque, Simijaca and Tausa located in the province of Ubaté in Cundinamarca are taken as a sample, where coal mining activity has a high participation in the region and in the national economy.